Techno-Pest Control Berbasis IoT untuk Proteksi Tanaman Padi - Dianna Ratnawati; Bayu Rahmat Setiadi (Jurnal Dinamika Vokasional Teknik Mesin, 2019)
Pest insects such as planthoppers and grasshoppers cannot be eradicated using pesticides. The objectives of this research are: (1) to produce a techno-pest control to repel or to exterminate planthopper and grasshopper pests; (2) to find out the impact of the use of said techno-pest control in controlling planthopper and grasshopper pests. The research methods being used is an experiment with a test-device at a distance of three and six meters. The technology being developed is based on the Internet of Things (IoT) which is set at a frequency of 40 kHz and is controlled via a smartphone. This technology is equipped with an IP camera to monitor the condition of the rice fields. The result of the trial at a distance of 3 meters could kill planthoppers and grasshoppers within 8 hours. Whereas at a distance of 6m it was able to kill planthoppers and grasshoppers within 13 hours. At the early stage, the insect pests showed a silent reaction because their metabolism was disrupted by the sound effects released by the device before the pests died. It can be concluded that techno-pest control is suitable to be used as an environmentally friendly technology to protect rice field from planthoppers and grasshoppers.Hama wereng dan belalang yang menyerang tanaman padi tidak mampu dimusnahkan dengan pertisida. Tujuan penelitian ini : (1) menghasilkan techno-pest control untuk mengusir/membasmi hama wereng dan belalang; (2) mengetahui dampak penggunaan techno-pest control dalam pengendalian hama wereng dan belalang. Metode yang digunakan adalah eksperimen dengan uji coba alat pada jarak 3m dan 6m. Teknologi yang dihasilkan berbasis IoT yang disetting pada frekuensi 40 kHz dan dikontrol melalui smartphone. Teknologi ini dilengkapi dengan IP camera sebagai monitoring kondisi sawah. Hasil uji coba pada jarak 3m mampu membunuh wereng dan belalang dalam waktu 8 jam. Sedangkan pada jarak 6m mampu membunuh wereng dan belalang dalam waktu 13 jam. Pada tahap awal hama menunjukkan reaksi diam karena metabolisme terganggu dengan efek suara yang dikeluarkan alat hingga hama mati. Sehingga dapat kesimpulan bahwa techno-pest control layak digunakan sebagai teknologi proteksi tanaman  padi dari hama wereng dan belalang yang ramah lingkungan.